Synthesis of Carboranyl-Containing β-Arylaliphatic Acids for Potential Application in BNCT - Lana I. Lissovskaya; Ilya V. Korolkov (Molecules)
One of the promising research areas involving carborane derivatives is boron neutron capture therapy (BNCT). Due to the high boron atom content in carborane molecules, these compounds are considered potential candidates for BNCT-based cancer treatment. Despite ongoing studies on various biologically active carboranyl-containing compounds, the search continues for substances that meet the stringent requirements of effective BNCT agents. In this study, the synthesis of carboranyl-containing derivatives of β-arylaliphatic acids is described, along with the investigation of their reactivity with primary and secondary amines, as well as with metals and their hydroxides. The molecular structures of the synthesized compounds were confirmed using Fourier-transform infrared (FTIR) spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, elemental analysis, and mass spectrometry (LC-MS). Cytotoxicity of the water-soluble compound potassium 3-(2-isopropyl-1,2-dicarba-closo-dodecaboran-1-yl)-3-phenylpropanoate was evaluated using several cell lines, including HdFn and MCF-7.